2018
DOI: 10.11158/saa.23.8.4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of on-host ticks (Acari: Ixodidae) in small mammals collected from forest near to human vicinity in Selangor, Malaysia

Abstract: Ticks are important vectors that transmit a variety of pathogenic microorganisms known to be medically important worldwide. Many vertebrate groups have become host to this organism, and their presence and abundance are an indicator of the condition of both host and its habitat. This study was conducted to determine tick’s infestation and its prevalence on small mammal’s residing in the recreational forests (RF) and semi-urban (SU) residential areas which have encountered Leptospirosis outbreak and cases in Hul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
(39 reference statements)
0
7
1
Order By: Relevance
“…Therefore, it may reveal higher ectoparasite infestation levels on female individuals host than male hosts. However, the findings contradicted the later studies of Kowalski et al (2015) and Ishak et al (2018b), where the infestation rate of ectoparasites on male hosts was higher than females of small mammals. Bantihun and Bekele (2015) reported that males often have a more extensive home range and can travel further, therefore, easily exposed to ectoparasites than females.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Therefore, it may reveal higher ectoparasite infestation levels on female individuals host than male hosts. However, the findings contradicted the later studies of Kowalski et al (2015) and Ishak et al (2018b), where the infestation rate of ectoparasites on male hosts was higher than females of small mammals. Bantihun and Bekele (2015) reported that males often have a more extensive home range and can travel further, therefore, easily exposed to ectoparasites than females.…”
Section: Discussioncontrasting
confidence: 89%
“…Unlike the four infested species that belong to the family Muridae, two species were not infested by any ectoparasites, namely T. glis and C. notatus from the families Tupaiidae and Sciuridae. Similar to Madinah et al (2014) and Ishak et al (2018b), these species exhibited a significantly low number of ectoparasite loads compared to Muridae. Rodents from the family Sciuridae are tree-top squirrel and spent most of the time on tree canopies, instead of on the ground (Thanee et al 2009).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…While many ticks in genus Ixodes are known to mate only in off-host environments, such as on vegetation, some Ixodes ticks belonging to the I. ricinus complex and I. angustus engage in off-and on-host copulation (Kiszewski et al 2001;Sonenshine and Coons 2014). Whereas I. granulatus is rarely collected off-host such as vegetations (Doi et al 2020) and offhost copulation of this tick has never been observed, Ishak et al (2018) previously reported that all adult male I. granulatus specimens were collected while cop- ulating with females on wildlife hosts. We also observed on-host copulation in this tick.…”
Section: Discussionmentioning
confidence: 90%
“…Black rats are known to be more arboreal than Norway rats, which are more ground-dwelling (Key and Woods 1996;Foster et al 2011), which may help black rats avoid infestation. However, Ishak et al (2018) reported the opposite results, recording I. granulatus infestation in black rats but not in Norway rats in the mainland of Malaysia. Similarly, Mori et al (2019) showed that black rats were infested by I. ricinus more intensively than Norway rats in the mainland of Italy.…”
Section: Discussionmentioning
confidence: 93%